Assessment of disease severity and patient prognosis in anti-GABABR encephalitis with and without comorbid tumors - Gao, Caiyun; Chen, Zhongyun; Huang, Huijin; Zhu, Runxiu; Su, Yingying (Frontiers in Neurology, 2023)
Purpose This study aimed to analyze the severity of the condition and prognosis of patients with anti-gamma-aminobutyric-acid type B receptor (anti-GABABR) encephalitis with tumors. Methods Patients with anti-GABABR encephalitis admitted to one of two hospitals from 2020 to 2022 were enrolled and divided into tumor and non-tumor groups. The clinical characteristics, condition severity, treatment options, and prognosis of the two groups of patients were compared and analyzed. Results Eighteen patients with anti-GABABR encephalitis were included, ten of whom had tumors. The comparison of clinical characteristics showed that rates of status epilepticus and coma were significantly higher in the group with tumors (P = 0.013 and P = 0.025, respectively); the incidences of pulmonary infection, respiratory failure, hyponatremia, and hypoproteinemia were also substantially more frequent in the tumor group (P = 0.054, P = 0.036, P = 0.015, and P = 0.025, respectively). The laboratory test result comparison showed that serum neuron-specific enolase (NSE) and carcinoembryonic antigen (CEA) were present only in the group with tumors (P = 0.036 and P = 0.092, respectively), but there was no significant difference in the occurrence of elevated CEA between the two groups. Conversely, the percentage of serum systemic autoimmune antibodies was higher in the group without tumors than in the group with tumors (P = 0.043). Patients with tumors tended to have poor outcomes (P = 0.152, OR: 7.000). Conclusion Severe brain damage and complications occur in patients with anti-GABABR encephalitis and comorbid tumors. Early screening for serum NSE and CEA helps in the early diagnosis and treatment of tumors. The prognosis is much worse for anti-GABABR encephalitis with tumors.